Medical Terms Involving药【yào】 Morpheme in Modern Chinese Language - Lola Akmalovna, Sultanova (International Journal of Psychosocial Rehabilitation, 2020)
For Chinese speakers, understanding medical terms, due to their descriptiveness, is not so difficult. The most difficult thing is actually translating medical terms into their native language. Chinese medicine is divided into traditional 中医 and Western 西医. This article discusses Western medical terminology with the participation of the morpheme 药【yào】. The main attention was paid to the neroglyphs in the abbreviated spelling (putonghua). Despite this, to explain the etymology of the hieroglyph, an analysis of the full outline of the character 药 was carried out along with some features of medical terms word formation with the participation of morpheme 药, such as 1) phrasing, 2) affix words, and 3) the formation of terms by reduction.